2021
DOI: 10.21037/hbsn-19-948
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes after hemihepatectomy for perihilar cholangiocarcinoma: does left or right side matter?

Abstract: Background: The only potentially curative option for patients with perihilar cholangiocarcinoma (PHC) is resection, typically an extrahepatic bile duct resection in combination with (extended) liver resection.Complications such as bile leakage and liver failure have been suggested to be more common after rightsided resections compared to left-sided resections, whilst superior oncological outcomes have been reported after right-sided resections. However, data on outcomes after right-sided or left-sided liver re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…On the other hand, previous authors suggested that right hepatectomy would be associated with better long-term survival because right hepatic pedicle resection enables better radicality compared with left resections (14,34,35). A recent review however, showed no survival benefit after either right or left resection for PHCC (36). This study has several limitations.…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, previous authors suggested that right hepatectomy would be associated with better long-term survival because right hepatic pedicle resection enables better radicality compared with left resections (14,34,35). A recent review however, showed no survival benefit after either right or left resection for PHCC (36). This study has several limitations.…”
Section: Discussionmentioning
confidence: 65%
“…Cholangiocarcinoma (CCA) is the most common biliary malignancy and the second most common primary liver malignant tumor, only after hepatocellular carcinoma ( 1 , 2 ). CCA accounts for 10–20% of deaths due to hepatobiliary malignancies ( 3 , 4 ). Usually, early diagnosis of CCA is challenging, as it has no specific symptoms; thus, it is mostly diagnosed at an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to either perform a right or left hepatectomy should be based on several factors, including tumor extension, presence of vascular infiltration, study of the future liver remnant (FLR) and center experience. Franken and colleagues reported their valuable experience with patients affected by PHC ( 2 ), comparing 76 left sided liver resections (LH) vs. 102 right sided liver resections (RH) for PHC, to highlight potential advantages of one approach over the other. Authors showed that no statistically significant differences could be found in both short- and long-term outcomes between the two groups.…”
mentioning
confidence: 99%